2011
DOI: 10.1007/s00192-011-1382-7
|View full text |Cite
|
Sign up to set email alerts
|

Goal attainment scaling in patients with lower urinary tract symptoms: development and pilot testing of the Self-Assessment Goal Achievement (SAGA) questionnaire

Abstract: SAGA may be used to identify treatment goals and assess goal-achievement in patients with LUTS in the clinic and for research (with additional validation). This information may promote patient-physician interaction and help patients establish realistic treatment goals, which may in turn improve treatment adherence and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…However, clinicians are confronted with the discrepancy between the treatment goal of health providers and treatment satisfaction of health receivers. To overcome this discrepancy, several studies developed treatment outcome measures including patients' subjective satisfaction and objective scales [9,10,11,12]. However, these systems have limitations concerning complexity and do not relate with the most bothersome symptom [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinicians are confronted with the discrepancy between the treatment goal of health providers and treatment satisfaction of health receivers. To overcome this discrepancy, several studies developed treatment outcome measures including patients' subjective satisfaction and objective scales [9,10,11,12]. However, these systems have limitations concerning complexity and do not relate with the most bothersome symptom [11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that GAS improves outcomes by helping patients develop realistic treatment goals and helping clinicians understand the importance of specific goals to each individual patient. It is anticipated that GAS could represent the innovative approach needed to evolve the management of OAB/LUTS …”
Section: History Of Goal‐attainment Scalingmentioning
confidence: 99%
“…Development of the Self‐Assessment Goal Achievement (SAGA) questionnaire, an instrument using GAS that was designed to help patients describe and prioritize their own treatment outcome goals, has been conducted in consideration of the stringent FDA requirements for validation of PROs . First, data were collected from women who had undergone pelvic reconstructive surgery on their pre‐operative goals and their post‐operative goal achievement .…”
Section: Development Of Saga Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…ОРИГИНАЛьНые ИССЛеДОВАНИя го процесса представляется адекватная оценка ожиданий пациентов от предстоящего хирур-гического вмешательства, поскольку она по-зволяет охарактеризовать их мнение о тяжести имеющегося заболевания [6,7]. Очевидно, что это позволит улучшить качество отношений между врачом и пациентом и таким образом персонализировать дальнейшее лечение.…”
unclassified